Protection of Geographical Indications of Local Indonesian Products from the Perspective of World Intellectual Property Organization - Sabrina, Ussy Gina; Gati, Rindri Andewi (KnE Social Sciences, 2025)
This research explores the development of innovative traditional knowledge aimed at addressing the intellectual property (IP) rights of indigenous peoples and local communities. As a regional initiative, supported by the World Intellectual Property Organization (WIPO) and its partners, it seeks to empower these communities in documenting, digitizing, and managing their cultural heritage on their own terms. Licensing and labelling frameworks are introduced to cater to the specific access and management requirements of indigenous, local, and traditional communities, offering standardized procedures and cultural heritage models. From a cultural research perspective, the study highlights batik as a representation of Indonesia’s cultural identity, emphasizing its ancestral significance and unique characteristics that distinguish it from other cultures. Using a normative, literature-based research method, this study underscores the importance of IP protection for the growth of Indonesia’s economy and the preservation of its cultural diversity. By safeguarding traditional knowledge and geographical indications, Indonesia can bolster its global economic and cultural standing. WIPO plays a pivotal role in this process, administering 24 treaties and fostering international cooperation to protect IP rights while promoting cultural and economic development worldwide.